2005
DOI: 10.1063/1.1866485
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent optical properties of sputter-deposited nanocrystalline p-type transparent CuAlO2 thin films

Abstract: Nanocrystalline, p-type semiconducting, transparent CuAlO2 thin films were deposited by direct current sputtering of a prefabricated polycrystalline CuAlO2 target, with deposition time as a variable parameter. Transmission electron micrographs reveal the formation of CuAlO2 nanoparticles. For the films deposited in 3, 9, and 15min, the average particle sizes are determined to be around 10, 20, and 30nm, respectively. The interplaner spacings calculated from selected area electron-diffraction patterns obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(52 citation statements)
references
References 40 publications
3
48
0
1
Order By: Relevance
“…Available experimental values for the optical band gaps of CuAlO 2 are quite disperse and range between 2.9 15 and 3.9 16 eV, where most studies point to a gap of 3.5-3.6 eV 4,17,18 . Theoretical studies point towards the existence of an indirect fundamental band gap that optically inactive due to symmetry reasons 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Available experimental values for the optical band gaps of CuAlO 2 are quite disperse and range between 2.9 15 and 3.9 16 eV, where most studies point to a gap of 3.5-3.6 eV 4,17,18 . Theoretical studies point towards the existence of an indirect fundamental band gap that optically inactive due to symmetry reasons 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently Gao et.al [3] observed the enhancement of electrical conductivity from 1 S/cm to 2.4 S/cm when the crystallite size was reduced to nanodimension. Techniques like pulsed laser deposition [2], ion exchange reaction [3] and sputtering [4] were widely used to synthesis single phase CuAlO 2 . Recently the author reported the synthesis of nanocrystalline CuAlO 2 by mechanical alloying process using Cu 2 O and α-Al 2 O 3 powders, the grain and grain boundary contribution electrical conductivities [5] and the existence of Debye type dielectric relaxation behaviour [6].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Thin lms have also been prepared by sputtering, using pulsed laser deposition from CuAlO 2 targets made by high temperature methods, and by interfacial reactions. [7][8][9][10][11] Additionally, more exotic methods such as polymer assisted deposition and fungus assisted synthesis have also been demonstrated. 12,13 Despite this rapid advance, many questions remain, particularly with respect to the intrinsic band gap and optical properties of this material.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies of the photoluminescence properties of CuAlO 2 have seldom been reported and the reports that are available are limited to room temperature luminescence measurements. 9,12,[14][15][16][17][18][19] At room temperature, thermal effects oen obscure important optical properties, which are essential for a comprehensive understanding of a material's properties. Furthermore, determination of the optical properties of a material via absorption measurements and Tauc plots can introduce signicant error if excitonic effects and surface scattering are important.…”
Section: Introductionmentioning
confidence: 99%